2005
DOI: 10.1093/qmath/hai017
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Lattice Points in Elliptic Annuli

Abstract: We study the distribution of the number of lattice points lying in thin elliptical annuli. It has been conjectured by Bleher and Lebowitz that, if the width of the annuli tend to zero while their area tends to infinity, then the distribution of this number, normalized to have zero mean and unit variance, is Gaussian. This has been proved by Hughes and Rudnick for circular annuli whose width shrink to zero sufficiently slowly. We prove this conjecture for ellipses whose aspect ratio is transcendental and strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…For α = 0, more detailed information about the distribution of S was obtained in [7]: under the condition that ρ → 0 and ρ T −δ for all δ > 0, it was shown that S has a Gaussian distribution. A similar result was established in [14] for "strongly" Diophantine rectangular lattices.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…For α = 0, more detailed information about the distribution of S was obtained in [7]: under the condition that ρ → 0 and ρ T −δ for all δ > 0, it was shown that S has a Gaussian distribution. A similar result was established in [14] for "strongly" Diophantine rectangular lattices.…”
supporting
confidence: 82%
“…On the other hand, Theorem 1.4 hinges on the asymptotic formula (14). We reiterate that Proposition 2.3 is the only ingredient of our proof that necessitates the Diophantine properties of α.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…[15,78,86,96,105,109,110,121,122] and references wherein). In fact, one can also consider the varying shapes RD R which includes both the Poisson regime where Vol(RD R ) does not grow (see [18] and references wherein) and the intermediate regime where Vol(RD R ) grows but at the rate slower than R d (see [54,127]).…”
Section: Higher Dimensional Actionsmentioning
confidence: 99%
“…both the Poisson regime where Vol(RD R ) does not grow (see [18] and references wherein) and the intermediate regime where Vol(RD R ) grows but at the rate slower than R d (see [54,127]).…”
Section: Higher Dimensional Actionsmentioning
confidence: 99%